2009
DOI: 10.1021/ja901231w
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Peptide Epoxyketones Are Recognized by Mammalian Proteasomes

Abstract: Proteasomes are multicatalytic proteinase complexes responsible for the degradation of cytosolic and nuclear proteins. In eukaryotes, proteasome substrates are normally marked for degradation through the attachment of ubiquitin chains at specific sites, and subsequent proteasome-mediated degradation takes place in a controlled and ATP-dependent fashion. 1 In mammals, some oligopeptides generated by proteasomes are presented to the immune surveillance system by major histocompatibility complex class I (MHC I) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…21 Notably, recent work from the Overkleeft group used epoxyketone ABPs to demonstrate that the proteasome, a multi-protein complex responsible for most regulated protein degradation in the cell, recognises glycosylated substrates. 40 This is an observation that may have widespread consequences given the importance of protein glycosylation in immunity, signalling and cellular recognition. The same group has recently elaborated ABPs against cathepsins with a mannose moiety, and shown that they can target professional antigen presenting cells that display cell surface mannose receptors.…”
Section: Abps Targeting Hydrolasesmentioning
confidence: 99%
“…21 Notably, recent work from the Overkleeft group used epoxyketone ABPs to demonstrate that the proteasome, a multi-protein complex responsible for most regulated protein degradation in the cell, recognises glycosylated substrates. 40 This is an observation that may have widespread consequences given the importance of protein glycosylation in immunity, signalling and cellular recognition. The same group has recently elaborated ABPs against cathepsins with a mannose moiety, and shown that they can target professional antigen presenting cells that display cell surface mannose receptors.…”
Section: Abps Targeting Hydrolasesmentioning
confidence: 99%
“…Treatment of murine EL4 cells with 18 was followed by cell lysis and exposure of the cell extracts to biotin-phosphane 19 , resulting in labeling of all six subunits. Following a related strategy, we demonstrated that O -GlcNAzylated peptide epoxyketones are recognized by proteasomes, indicating that the proteasome might also be able to turn over O -GlcNAcylated proteins, with possible consequences for antigen presentation processes.…”
Section: Activity-based Protein Profiling: Direct Versus Two-step Lab...mentioning
confidence: 98%
“…107 We used an ABP-based strategy to study whether the proteasome can handle such substrates. 108 The selective proteasome inhibitor epoxomicin was N-terminally elongated with O-GlcNAc-Ser derivative and equipped with an azidoacetyl group which could be modified with biotin for visualization purposes (probes 99-102, Fig. 24).…”
Section: Alternative Degradation Pathwaysmentioning
confidence: 99%